2007
DOI: 10.1074/jbc.m704043200
|View full text |Cite
|
Sign up to set email alerts
|

SLP-65 Signal Transduction Requires Src Homology 2 domain-mediated Membrane Anchoring and a Kinase-independent Adaptor Function of Syk

Abstract: The SH2 domain-containing leukocyte adaptor proteins, SLP-65 (1) (BLNK (2), BASH (3)), and SLP-76 (4), are instrumental to integrate and collect signals from antigen receptors on B and T lymphocytes, respectively. In their N-terminal half, the two effector proteins encompass a variety of similar consensus motifs for either inducible tyrosine phosphorylation by Syk/ ZAP-70 family kinases or constitutive association to proteins with Src homology (SH) 3 3 domains. Both SLP adaptors possess a C-terminal SH2 domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…Likewise, in normal cells, the importance of the adapter function of ZAP-70 has been shown for the development of immature CD4 ϩ CD8 ϩ thymocytes having limited expression of LCK (37). In SYK, the importance of an adapter function for calcium mobilization was demonstrated in the chicken cell line DT-40 cells as well as in mouse B lymphocytes (29,33). In a recent report, suppression of Treg cells was also demonstrated to be independent of ZAP-70 kinase activity (38).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in normal cells, the importance of the adapter function of ZAP-70 has been shown for the development of immature CD4 ϩ CD8 ϩ thymocytes having limited expression of LCK (37). In SYK, the importance of an adapter function for calcium mobilization was demonstrated in the chicken cell line DT-40 cells as well as in mouse B lymphocytes (29,33). In a recent report, suppression of Treg cells was also demonstrated to be independent of ZAP-70 kinase activity (38).…”
Section: Discussionmentioning
confidence: 99%
“…S1) (11,12). To investigate the underlying mechanism, we visualized the subcellular distribution of citrine-tagged versions of wild-type and N-terminally truncated SLP-65 (DN-SLP-65) with laser scanning confocal microscopic analysis of resting and BCR-activated transductants of the chicken B cell line DT40 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mutational analyses showed that a short N-terminal SLP-65 segment of about 50 amino acid residues is indispensable for SLP-65 signaling (11). Furthermore, deletion of the N terminus of SLP-65 interfered neither with the functionality of the SLP-65 SH2 domain nor with the ability of SLP-65 to form a complex with CIN85 (12,13). These findings demonstrated that, in addition to the SH2 domain and the CIN85-binding sites, the N-terminal region of SLP-65 constitutes a third and separate targeting device that controls a nonredundant route of SLP-65 activation.…”
Section: Introductionmentioning
confidence: 99%
“…This enables SLP-65 to nucleate the formation of a multiprotein complex by recruiting several SH2 domain-containing effector proteins such as phospholipase (PLC)-␥2 and Bruton's tyrosine kinase (21). SLP-65 not only assembles this signalosome but is also critical for its stimulation-induced translocation from the cytosol to the plasma membrane (22,23). Assembly and membrane targeting of this complex are both requisites for PLC-␥2 to hydrolyze membrane phospholipids resulting in the generation of diacylglycerol and inositol triphosphate, which in turn induces the release and entry of Ca 2ϩ ions from intra-and extracellular sources, respectively (24 -26).…”
mentioning
confidence: 99%